POLA ASUH BERBASIS KARMA YOGA: MENDIDIK ANAK DENGAN TANGGUNG JAWAB DAN DEDIKASI (Haridracarya: Journal of Hindu Religious Education, 2023)
This study examines the integration of Karma Yoga principles in parenting and its effects on child development, focusing on how this approach influences the formation of values such as responsibility, dedication and integrity. Rooted in Hindu philosophy, Karma Yoga emphasizes the importance of actions performed with good intentions and without expectations of personal outcomes, offering a unique perspective in supportive and warm parenting. The results indicate that applying Karma Yoga principles, including Nishkama Karma, Duty without Attachment, Selflessness, Mindfulness and Presence, creates a nurturing parenting environment where children can develop a sense of responsibility, empathy, independence and also assists parents in their journey towards personal growth and spiritual awareness. This research provides valuable insights into the application of philosophical principles in modern parenting, offering a process-centered and authentic approach to support the healthy and harmonious development of children within the context of the modern family
Keywords: Karma Yoga; Parenting; Child Development